Mobilization of the environment concept on sixth grade students - Fonseca Rincón, Jenny Natalia; Molano Carrera, Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The preliminary results of the project Mobilization of the environment concept in sixth grade students are presented, specifically the results of the conceptual exploration about the environment. The objective of the project is the design and construction of a pedagogical and didactic proposal that contributes to the mobilization of the concepts of environment installed in students towards a systemic vision of the same and that is pertinent to the formative intentions of the School Environmental Project (SEP). The project is carried out under the socio critical paradigm, with a qualitative research approach and research action methodology, with a sample of 29 students between the ages of 11 and 13 belonging to one of the three sixth grade groups of the “Enrique Olaya Herrera” Educational Institution in Guateque (Boyacá, Colombia). Twentyone (21) students made a drawing and an explanatory text, based on the question, what is the environment for you? The categorization of the answers allowed us to conclude that the results coincide with what was reported in the background check: the students do not establish interactions between components of the environment and focus their responses on an anthropocentric and naturalistic vision of the same. These results confirm the need to build a pedagogical and didactic proposal that allows the understanding of the concept environment from a systemic vision.